A CEFR-Based Analysis of Speaking Proficiency in 9th Grade Arabic Textbooks - Utami, Resgi Widati Tria Lis; Shodiq, Muhammad Jafar (Al-Arabi: Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2024)
This research was conducted because there is no availability of learning materials that are able to support the needs of students in improving their understanding and skills of Arabic, especially in  mahārah kalām . The research method used is library research with primary data in the form of Arabic teaching materials and secondary data in the form of relevant scientific articles. Data analysis techniques in this study consisted of data collection, data reduction, data display, and drawing conclusions. The results of this study indicate that the Arabic language textbooks for class IX for junior high schools published by KEMENAG in 2020 meet the eligibility standards of books according to the BSNP. And in the CEFR realm, the Arabic textbook contains language proficiency levels at A2 and B1 in mahārah kalām. The results of this research can add to teachers’ insight regarding the availability of learning media that is appropriate to the learning level students in mahārah kalām.